Defect Engineering in MoSe2 for the Hydrogen Evolution Reaction: From Point Defects to Edges - Shu, Haibo; Zhou, Dong; Li, Feng; Cao, Dan; Chen, Xiaoshuang (ACS applied materials & interfaces, 2017)
Superior catalytic activity and high chemical stability of inexpensive electrocatalysts for the hydrogen evolution reaction (HER) are crucial to the large-scale production of hydrogen from water. The nonprecious two-dimensional MoSe2 materials emerge as a potential candidate, and the improvement of their catalytic activity depends on the optimization of active reaction sites at both the edges and the basal plane. Herein, the structural stability, electrocatalytic activity, and HER mechanisms on a series of MoSe2 catalytic structures including of point defects, holes, and edges have been explored by using first-principles calculations. Our calculated results demonstrate that thermodynamically stable defects (e.g., VSe, VSe2 , SeMo, and VMo3Se2 ) and edges (e.g., Mo-R and Se-R) in MoSe2 are very similar to the case of MoS2, but their HER activity is higher than that of the corresponding structures in MoS2, which is in good agreement with experimental observations. Furthermore, a Fermi-abundance model is proposed to explain the fundamental correlation between the HER activity of various MoSe2 catalysts and their intrinsic electronic structures, and this model is also applicable for assessing the HER activity of other types of catalysts, such as MoS2 and Pt. Moreover, two different HER mechanisms have been revealed in the MoSe2 catalytic structures: the Volmer–Tafel mechanism is preferred for the VSe and VSe2 structures, whereas the Volmer–Heyrovsky mechanism is more favorable for other MoSe2 catalytic structures. The present work suggests that MoSe2 with appropriate defects and edges is able to compete against the Pt-based catalysts and also opens a route to design highly active electrocatalysts for the HER.